Identifikasi dan Pengelolaan Risiko Pelayanan Farmasi di Rumah Sakit: Studi Deskriptif - Muharani, Defrika; Arrasily, Nailul Fithry; Minarsih, Tri Jenny; Faizah, Hashifah; Farhiyah, Nur Laili; Hartono, Budi; Daud, Alfani Gusta (SENTRI: Jurnal Riset Ilmiah, 2026)
Pharmacy services in hospitals are a vital component of healthcare systems, aiming to ensure the safe, rational, and efficient use of medicines. The increasing complexity of pharmacy operations elevates the likelihood of various risks in both clinical and operational domains. This study provides a descriptive analysis of the types of risks inherent in hospital pharmacy services and the corresponding risk management efforts based on empirical evidence. Findings reveal that medication errors are the most prevalent clinical risk, particularly during prescribing, preparation, and administration phases, potentially compromising patient safety and therapeutic outcomes. Operational risks also present significant challenges, as indicated by high levels of dead stock and expired medicines, reflecting weaknesses in forecasting and inventory control. Key contributing factors include limited human resources, suboptimal information systems, and high workload pressures. Additionally, barriers to incident reporting due to a punitive organizational culture hinder effective risk mitigation. Although the management of pharmaceutical risks is mandated by the Ministry of Health Regulation No. 72 of 2016, its implementation effectiveness remains constrained and demands improvement through integration of digital technologies, enhancement of pharmaceutical workforce competencies, and cultivation of a strong patient safety culture. These insights underscore the necessity for comprehensive strategies to foster pharmacy services that are safe, effective, and efficient.